β-glicana : extração, caracterização e uso como microencapsulante de Ilex paraguariensis para avaliação biológica in vitro - Werlang, Stéfani (2021)
The prevalence of chronic non-transmissible diseases has increased public awareness in recent decades regarding the incorporation of natural and functional products in the diet. Polyphenols have demonstrated several health benefits, such as reducing cholesterol, increasing immune system and treating intestinal disorders. To phenolics confer benefits to human health, guarantee the bioactivity in the conditions of the gastrointestinal tract is extremely necessary. The encapsulation of bioactive compounds in a nondigestible food material is of great importance for food industry and research. β-glycan is a polysaccharide that can be used as an encapsulating agent for the controlled release of bioactive compounds. The objective was to evaluate the potential of β-glycan as an encapsulating agent of yerba mate for controlled release of bioactive compounds, bioaccessibility and in vitro biological activities. The extraction of β-glycan from white oats was optimized using a factorial design 32, evaluating the particle size and agitation speed on the purity and extraction yield. Microencapsulation was based on a factorial design 23, evaluating the concentration of wall material, yerba-mate extract and glycerol in the washing solution. The microcapsule with greater encapsulation efficiency (EE), spectrum FTIRand thermal stability was evaluated for its morphology, pH stability, antioxidant and anti-inflammatory activities. The optimization of β-glycan extraction showed a maximum yield of 50.87% and purity of 62.43%, with the smallest particle size and highest agitation rate. The use of 1% β-glycan, 0.5% yerba mate extract and 5% glycerol in the washing solution showed greater EE (67.53%), with smoothed and spherical capsules, and also a high thermal stability (300 ° C). The release of phenolic compounds was increased on alkaline pH (15.38 mg EAG / mL), due to the breaking of the capsule at pH 8.2. The microcapsule inhibited heat-induced hemolysis (42.44%), hypotonicity (51.66%), proteinase (70%) and protein denaturation (72%). The capacity of inhibiting these parameters suggests that the microcapsule has anti-inflammatory potential as effective as the diclofenac, featuring an alternative to control and prevent inflammatory responses.